Prevalence of Reproductive Problems under different Dairy Production Systems - Patel, Diksha; Ponnusamy, K. (Indian Journal of Extension Education, 2018)
The present study was conducted in Haryana, Madhya Pradesh and Chhattisgarh representing three different dairy production systems namely: dynamic, transient and subsistence dairy production systems of India respectively during 2017-18. Data were collected personally, from 30 Veterinary Officers (VO)by personal interview.Among 10 major reproductive problems of female animals, late sexual maturity with RBQ value 92 and anestrus (82) in non-descript; anestrus (94) and late sexual maturity (76) in indigenous; repeat breeding (82) and anestrus (67) in crossbred; and anestrus (94) and repeat breeding (82) in Buffalo were ranked first and second reproductive problems respectively in Haryana state. Whereas in case of Madhya Pradesh the non-descript cattle; indigenous cattle; crossbred cattle and buffalo breed were mainly affected by late sexual maturity (94) and anestrus (88); anestrus (92) and late sexual maturity (85); repeat breeding (88) and anestrus (70) and late sexual maturity (94) and anestrus (87) were ranked by respondents respectively. Late sexual maturity (78) and uterine infections (77); late sexual maturity (88) and anestrus (85); uterine infections (73) and abortion (67); late sexual maturity (90) and anestrus (83) were ranked the first and second reproductive problems in non-descript cattle; indigenous cattle; crossbred cattle and buffalo respectively in Chhattisgarh. Constraints analysis revealed that treatment of dairy animals by village-quacks was the important constraint reported by veterinary officers (V.Os) of Haryana and lack of awareness of farmers for reproductive problems of dairy animal was the most important constraint as perceived by V.Os of both Madhya Pradesh and Chhattisgarh.Sincestate-level variation could be observed in prevalence of reproductive problems as well as constraints experienced by V.Os; state centric extension plan should be prepared to reduce the prevalence of reproductive problems of animals and constraints of veterinary officers.
Keywords: Constraints; dairy production systems; rank based quotient; reproductive problems